Demonstration of X-ray Thomson scattering as diagnostics for miscibility in warm dense matter - S. Frydrych (Nature Portfolio, 2020)
It is challenging to reliably probe the miscibility behavior of elements in extreme conditions. Here, the authors use X-ray Thomson scattering and compare to the X-ray diffraction method in order to determine mixing of different atomic species in warm dense matter conditions.